2018
DOI: 10.3390/aerospace5020066
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Fidelity Approach for Aerodynamic Performance Computations of Formation Flight

Abstract: This paper introduces a multi-fidelity computational framework for the analysis of aerodynamic performance of flight formation. The Vortex Lattice and Reynolds Averaged Navier-Stokes methods form the basis of the framework, as low-and high-fidelity, respectively. Initially, the computational framework is validated for an isolated wing, and then two rectangular NACA23012 wings are considered for assessing the aerodynamic performance of this formation; the optimal relative position is through the multi-fidelity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…CFD methodology [25][26][27][28][29][30][31][32] citations (52,19,12,40,3,6,5,20) CFD tool [33] citations (16) CFD and experiment [34] citations (14) multicopter dynamics and experiment [35] citations (35) Different hyperparameters mesh size [36][37][38] citations (1,60,55)…”
Section: Different Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…CFD methodology [25][26][27][28][29][30][31][32] citations (52,19,12,40,3,6,5,20) CFD tool [33] citations (16) CFD and experiment [34] citations (14) multicopter dynamics and experiment [35] citations (35) Different hyperparameters mesh size [36][37][38] citations (1,60,55)…”
Section: Different Algorithmsmentioning
confidence: 99%
“…In addition to different algorithm applications in materials science and aerospace science, different computational fluid dynamics (CFD) methodologies or different CFD tools (Q3D and MATRICS-V [33]) are commonly used to obtain MF data. Reynolds-Averaged Navier-Stokes (RANS) method is commonly used to obtain HF data [30][31][32], and the potential flow model to obtain LF data [26,29]. In reference [25], RANS is used to obtain LF data, while large-eddy simulations are used to obtain HF data.…”
Section: Multi-fidelity Data From Different Algorithmsmentioning
confidence: 99%
“…Insights in a vast number of available references such as [2][3][4][5][6][7][8][9] support the decision of the authors of this paper to finally adopt the tandem wing (TW) configuration for the new UAV. Namely, in the case of classical concepts, the horizontal tail most often generates negative lift in order to provide proper trim in cruising flight.…”
Section: Introductionmentioning
confidence: 99%
“…As trailing aircraft is the beneficiary, its position in the formation must be determined and maintained during the vortex surfing phase to maximize the gains. Other than the flight test, several numerical simulations research [25][26][27][28] have been conducted over the last few decades to investigate the trailing aircraft position and its aerodynamics implications on vortex surfing. With the available data from SAVE program, Halaas et al [25] used Reynolds-Averaged Navier Stokes (RANS) for the C-17 formation simulation, with consideration on the trim condition of following aircraft.…”
Section: Introductionmentioning
confidence: 99%
“…The authors have validated the RANS simulation estimated mean values result against the actual flight test data with 95% confidence on the wake dynamics. Singh et al [26] used a multi-fidelity CFD simulation on blended-wing-body UAVs in close tandem formation flight. The authors found that both the Vortex Lattice Method (VLM) and RANS turbulence models predict the same location of minimum drag and maximum lift, but RANS is more accurate in the lift and drag calculation, with a smaller deviation from the experimental results.…”
Section: Introductionmentioning
confidence: 99%